Comparison of the Sorption of Trifluoromethane (R-23) on Zeolites and in an Ionic Liquid - Mark B. Shiflett; David R. Corbin; A. Yokozeki (Adsorption Science & Technology)
In this study, trifluoromethane (R-23) has been adsorbed on three zeolites, namely 5A, LSX and 13X, and their adsorption isotherms have been measured at approximately 298 and 323 K using a gravimetric microbalance. All cases belong to the adsorption Type II (one of the six IUPAC classifications), and the adsorption (and desorption) processes are reversible. Three different adsorption models [original Langmuir, multi-site Langmuir and BET equations] have been adopted to analyze the data, with a particular interest in calculating the heat of adsorption (–ΔH), which was found to be about 10, 30 and 40 kJ·mol −1 for zeolite 5A, LSX and 13X, respectively. These values are within the range of typical physical adsorptions. Solubility of R-23 in ionic liquid 1-octyl-3-methylimidazolium 1,1,2,2-tetrafluoroethanesulfonate ([omim][TFES]) has been measured at approximately 298 and 323 K using the same gravimetric microbalance and the value was compared with the adsorption results. The solubility capacity of R-23 in ionic liquid reaches about 3 mol kg −1 around 2.5 MPa at 298 K, while the adsorption capacity on zeolites becomes around 3 mol kg −1 at around 0.25 MPa (ten times smaller). The adsorption on zeolites took more time than the absorption in the ionic liquid to reach thermodynamic equilibrium.